Kinetics of functional beta cell mass decay in a diphtheria toxin receptor mouse model of diabetes - van Krieken, Pim P. (2018)
Functional beta cell mass is an essential biomarker for the diagnosis and staging of diabetes. It has however proven technically challenging to study this parameter during diabetes progression. Here we have detailed the kinetics of the rapid decline in functional beta cell mass in the RIP-DTR mouse, a model of hyperglycemia resulting from diphtheria toxin induced beta cell ablation. A novel combination of imaging modalities was employed to study the pattern of beta cell destruction. Optical projection tomography of the pancreas and longitudinal in vivo confocal microscopy of islets transplanted into the anterior chamber of the eye allowed to investigate kinetics and tomographic location of beta cell mass decay in individual islets as well as at the entire islet population level. The correlation between beta cell mass and function was determined by complementary in vivo and ex vivo characterizations, demonstrating that beta cell function and glucose tolerance were impaired within the first two days following treatment when more than 50% of beta cell mass was remaining. Our results illustrate the importance of acquiring quantitative functional and morphological parameters to assess the functional status of the endocrine pancreas.